"Are They Here Legally?" Institutional Intersectionality in Migrant Advocacy Coalition Work. Issue 1 (1st January 2022) - DeTurk, Sara
Abstract : Based on participant observation and semi-structured interviews with resettlement agencies, volunteer organizations, and refugees, this study examined the rhetorical tactics of outreach and advocacy as well as the dynamics of inter-organizational collaboration. Organizations supporting international migrants have different institutional priorities which face pressures by multiple socializing institutions. These operate intersectionally, such that the status of migrants and rhetorical support for them are circumscribed by a recursive relationship between government policies and linguistic labels. The article addresses an important contemporary social problem and articulates an expansion of intersectionality theory within the communication discipline, as well as its implications for coalition work.